Possible Protective Effects of Saw Palmetto Extract in Indomethacin Treated Rats - Abdul Majeed, Zaid M.; Al-Atrakji, Mohammed Q. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Indomethacin is a widely used nonsteroidal anti-inflammatory drug for treating pain and fever. It is coupled with oxidative stress and an inflammatory response, which accounts for several detrimental effects on the body’s organs.Objectives: This study aimed to assess the potential of using SSaw palmetto extract to counteract the oxidative stress and inflammatory response resulting from Indomethacin treatment in rat models.Methods: The study involved 20 male albino rats, arbitrarily sorted into four groups of 5 animals each group. Group 1 (control group) was neither induced nor treated. Groups (2-4) were treated with oral Omeprazole (20 mg/kg/day) and Saw palmetto extract (20 mg/kg/day) suspensions, respectively, for 15 days. On day 15 of the study, blood samples were taken by heart puncture for the determination of superoxide dismutase, glutathione peroxidase, tumor necrosis factor-alpha, and interleukin-6.Results: Saw palmetto extract treatment was found to elevate serum levels of superoxide dismutase and glutathione peroxidase significantly compared to the Indomethacin-induction group. Conversely, tumor necrosis factor-alpha and interleukin-6 levels were markedly reduced compared to the Indomethacin-induction group. The antioxidant and anti-inflammatory activities of Saw palmetto extract are contingent on its bioactive flavonoids and sitosterols content.Conclusion: The antioxidant and anti-inflammatory influence of Saw palmetto extract could be a promising approach to counteract oxidative stress and inflammatory response due to Indomethacin treatment.